2002
DOI: 10.1046/j.1365-3016.2002.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal characteristics associated with place of delivery and neonatal mortality rates among very‐low‐birthweight infants, Georgia

Abstract: To determine whether the Healthy People 2000 objective to deliver very-low-birthweight (VLBW) infants at subspecialty perinatal care centres was met, and if improvements in the regional perinatal care system could reduce neonatal mortality further for 2010, we examined place of delivery for VLBW infants, associated maternal characteristics and the potential impact on neonatal mortality. We used linked birth and death records for the 1994-96 Georgia VLBW (i.e. 500-1499 g) birth cohorts. Among 4770 VLBW infants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 23 publications
3
46
1
4
Order By: Relevance
“…The high frequency of out-born infants in this report is similar to findings reported by Samuelson et al 15 They found that patients living away from subspecialized centers in Georgia had a higher risk for delivering their VLBW infants outside these centers, potentially subjecting the infants to additional morbidity and mortality. 15 Distance of the maternal residence from a subspecialty center was reported to be associated with birth of VLBW infants in level I nurseries in other population based studies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The high frequency of out-born infants in this report is similar to findings reported by Samuelson et al 15 They found that patients living away from subspecialized centers in Georgia had a higher risk for delivering their VLBW infants outside these centers, potentially subjecting the infants to additional morbidity and mortality. 15 Distance of the maternal residence from a subspecialty center was reported to be associated with birth of VLBW infants in level I nurseries in other population based studies.…”
Section: Discussionsupporting
confidence: 90%
“…15 Distance of the maternal residence from a subspecialty center was reported to be associated with birth of VLBW infants in level I nurseries in other population based studies. 15,17,23 Obviously, distance to care may present a larger impediment to women with less social capital (e.g. low income, transportation or community resources).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Independent of hospital level, other hospital factors remained significantly associated with nontransfer of <1250 g infants in the 19 infants less than 1250 g were to be transferred to Level III perinatal centers when born at a Level I or Level II hospital, and also when born at a Level II þ hospital if the Level II þ hospital's exception status did not include infants less than 1250 g. Based on the data presented here, the rate of nontransfer of these infants was 40.4%, with the highest overall rates of nontransfer occurring among infants weighing 1000-1249 g. While the mortality rates among nontransferred versus transferred infants were not examined in the current study, previous studies have demonstrated that the risk of death is higher for infants less than 2000 g, 11,21 infants less than 1500 g, 18,22 and infants less than 1250 g 13 born at Levels I and II centers rather than tertiary care centers. In addition, in a study of perinatal regionalization in Illinois from 1991 to 1993, 23 a lower proportion of VLBW infants (<1500 g) transferred out was associated with an increase in neonatal mortality.…”
Section: Resultsmentioning
confidence: 80%